2013
DOI: 10.1590/s0104-66322013000100020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mass transfer on MHD flow of casson fluid with chemical reaction and suction

Abstract: -Effect of mass transfer in the magnetohydrodynamic flow of a Casson fluid over a porous stretching sheet is addressed in the presence of a chemical reaction. A series solution for the resulting nonlinear flow is computed. The skin friction coefficient and local Sherwood number are analyzed through numerical values for various parameters of interest. The velocity and concentration fields are illustrated for several pertinent flow parameters. We observed that the Casson parameter and Hartman number have similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
72
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(81 citation statements)
references
References 24 publications
3
72
0
Order By: Relevance
“…The biofluid is taken to be blood and following values of the parameters (with corresponding SI units) are considered (following Shehzad et al 19 ): These values correspond to very weak inertial effects whereas the value of Sc, is a reasonable approximation for pharmaceutical species. Table I shows the convergence of our numerical results for U (η) with the above mentioned values of the governing parameters at t = 0.3, as the step-size h decreases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The biofluid is taken to be blood and following values of the parameters (with corresponding SI units) are considered (following Shehzad et al 19 ): These values correspond to very weak inertial effects whereas the value of Sc, is a reasonable approximation for pharmaceutical species. Table I shows the convergence of our numerical results for U (η) with the above mentioned values of the governing parameters at t = 0.3, as the step-size h decreases.…”
Section: Resultsmentioning
confidence: 99%
“…Further, the oscillatory pressure gradient has been considered to model the heart pumping phenomenon, whereas the Darcy-Forchhmeir model has been considered for the porous structure (cholesterol and blood clots) inside the artery. In recent years, many researchers have pointed out that the Casson fluid model is the most appropriate one for modeling the blood flow in different geometries (Shehzad et al 19 and Boyd el al. 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Attia and SayedAhmed [19] considered the Couette flow of electrically conducting Casson fluid between parallel plates. Effect of mass transfer on MHD flow of Casson fluid was discussed analytically by Shehzad et al [20]. Taylor's series was employed in 2 Journal of Applied Mathematics order to solve nonlinear differential equations.…”
Section: Introductionmentioning
confidence: 99%
“…The relevant equations are first derived, and the series solutions are constructed by the homotopic procedure. Shehzad et al [5] analysed the effect of mass transfer in the magnetohydrodyanamic flow of a Casson fluid over a porous stretching sheet in the presence of a chemical reaction and suction. It is observed that the Cassion parameter and Hartman number have similar effects on the velocity in a qualitative sense.…”
Section: Introductionmentioning
confidence: 99%